CRUDE INCOMPATIBILITY PROBLEMS AT HEAVY CRUDE UNIT DESALTER - Kirmani, Z.; Khurshid, A.; Alam, N.; Gul, S.; Ahmed, N. (The Nucleus, 2020)
Attock Refinery Limited (ARL) is based at Rawalpindi, Pakistan and operates a 40,000 Barrels per Stream Day (BPSD) refinery. The Heavy Crude Unit (HCU) of ARL is a fully integrated two-stage 10,000 BPSD Atmospheric and 5,700 BPSD Vacuum Distillation Unit. A 3-stage desalter designed to reduce salt and BS&W content from 2,000 parts per thousand barrels (PTB) and 2% to less than 5 PTB and 0.1% respectively, is part of HCU. The feedstock is a composite blend of 14 local Heavy Crudes received at the Refinery. Although in the past this desalter had been giving good performance, over the last one year, period since August 2005, at least nine shutdowns of the unit took place due to salt slippage and consequential tube leakages at the overhead Crude-Naphtha vapor Heat Exchanger where partial condensation of naphtha takes place. Final condensation is achieved in trim condenser. High salted water carry-over with the crude caused increased hydrolysis, formation of Hydrochloric acid and increase of tail water chlorides. Salt contents at the outlet of 3rd desalter at times increased up to 400 PTB with 3.2% BS&W during the above mentioned upsets, as compared to normal 5-10 PTB. Fallout from this loss of desalter control was the creation of large quantities of slop due to draining of strong water oil emulsion from the desalters. Individual crudes of the blend were analyzed for affinity of water and emulsion stability. It was observed that 3 of the 14 crudes formed very strong while the remaining crudes formed weak oil water emulsion, which easily separated water from oil in desalter without any operational problem. Study was further narrowed down to one crude evaluation. Alkaline earth metallic naphthenate surfactants were detected and isolated as responsible for the strong water oil and sediments emulsion. The isolated crude was next withdrawn from the Heavy Crude blend. As soon as it was isolated and its ratio in heavy crude tank came down to 0.7 %, the problem began to be controlled, along with other operational measures taken, namely, increase of demulsifier dosage 50 liters/day in first desalter vessel and also 10 liters/ day in third desalter vessel, start of low chlorides tail water injection in desalter wash water, discontinuation of ammonia injection, and addition of Neutralizer and Filmer. This paper gives a detailed analysis of the problem and how it was successfully tackled by the Engineers & Chemists at ARL.